Linking organizational intangibles to sustainable performance: A mediated-moderated model from the hospitality industry - Siagian, Mauli; Brahmasari, Ida Aju; Mujanah, Siti (Edelweiss Applied Science and Technology, 2025)
The hospitality sector in Batam drives the local economy by creating jobs, increasing incomes, and supporting local businesses through collaboration with vendors. While maintaining service quality remains challenging, competition among hotels encourages innovation. Adapting to technology and sustainability trends helps the sector thrive in tourism development. This research examines how organizational culture, knowledge management practices, and organizational learning impact human resource management practices, job satisfaction, and sustainable organizational performance, with organizational climate as a moderator. The study surveyed 233 out of 557 employees from star-rated hotels in Batam, using structural equation modeling with AMOS 20 for data analysis. The results show that organizational culture and knowledge management practices significantly influence human resource management practices (HRMP), while organizational learning does not. Organizational culture does not significantly affect job satisfaction, but knowledge management practices and organizational learning do. Organizational culture does not significantly impact sustainable organizational performance, whereas knowledge management practices and organizational learning positively do. HRMP significantly affects sustainable organizational performance, while job satisfaction does not. Organizational climate does not moderate the effect of HRMP on sustainable organizational performance but moderates the effect of job satisfaction on it. HRMP mediates the influence of organizational culture and knowledge management practices on sustainable organizational performance but does not mediate the effect of organizational learning. Job satisfaction does not mediate the effects of organizational culture, knowledge management practices, or organizational learning on sustainable organizational performance.